THE PRECESSION OF ASTEROID 1620 GEOGRAPHOS - Prokof’eva, V. V.; Tarashchuk, V. P.; Karachkina, L. G. (Одеські астрономічні публікації, 2017)
The frequency analysis of the fine photometric effects in the photometric observation obtained during asteroid 1620 Geographos approaching to Earth in 1994 allowed to derive the precession of asteroid spin axis. The periods of 0d.8 and 2d.8 or multiple to them were revealed. The magnitude of precession angle was estimated to be near 3°. The nature of the precession discussed. The emergence of the free precession may be supported at time of the formation of the asteroid or by the collision with another body. The forced precession does not contradict to the Geographos connection with meteor streams and the assumption that Geographos may have small satellites.